2013
DOI: 10.7241/ourd.20132.37
|View full text |Cite
|
Sign up to set email alerts
|

A study on efficacy of oral zinc therapy for treatment of acrodermatitis enteropathica

Abstract: Introduction: Acrodermatitis enteropathica (AE) is a disorder of zinc metabolism that occurs in one of two forms: an inborn (congenital) form and an acquired form. The inborn form of AE is a rare genetic disorder characterized by intestinal abnormalities that leads to inability to absorb zinc from the intestine. The lack of zinc presents, characteristically, as skin inflammation with pustules occurring around the mouth and/or anus, diarrhea. Aims: To study the efficacy of oral zinc therapy on thirty patients o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It has been suggested that zinc inhibits hair regression and accelerates recovery of the hair follicle [ 14 ]. For instance, acrodermatitis enteropathica, a rare genetic disorder due to malabsorption of zinc clinically presents with hair loss [ 14 , 15 ]. However, the association between zinc and hair loss is still controversial [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that zinc inhibits hair regression and accelerates recovery of the hair follicle [ 14 ]. For instance, acrodermatitis enteropathica, a rare genetic disorder due to malabsorption of zinc clinically presents with hair loss [ 14 , 15 ]. However, the association between zinc and hair loss is still controversial [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the current published study shows, the simple and cheap therapy consisting of supplementation of zinc is effective in the treatment of this disease [8]. Author clearly described the complexity of clinical manifestation of acrodermatitis enteropathica, which involves not only the skin changes but also gastrointestinal and psycho-neurological changes and disturbances.…”
Section: Comment To the Articlementioning
confidence: 97%
“…According to World Health Organisation 2001 report, the global burden of disease indicated that skin diseases were associated with mortality rates of 20,000 in Sub-Saharan Africa in 2001 [9]. An additional point, often overlooked, is that skin problems in the developing world are often transmissible and contagious but are readily treatable [10,11]. Bacterial skin infections or pyoderma are common in most developing countries arised as primary infections of the skin (impetigo) or secondary infections among adolescents [12,13].…”
Section: Introductionmentioning
confidence: 99%